Characterization of the anti-angiogenesis activity of labisia pumila and identification of its molecular constituents that contribute to its biological activity. - Samad, Nozlena Abdul (2010)
Angiogenesis is a process of new blood vessel formation. Inhibition of angiogenesis is considered one of the most promising strategies in treating variety of illnesses including cancer. Labisia Pumila var. alata (Myrsiaceae) or locally known as ‘kacip fatimah’, a lowland plant, is used widely by the Malays in Peninsular Malaysia to treat many health problems and ailments.